Industrial Scale RTD Measurement Using Gold Radiotracer - Meenakshi Sheoran (Iranian Journal of Chemistry & Chemical Engineering, 2021)
Residence Time Distribution (RTD) is a suitable method to find out the hydrodynamics of any industrial or lab-scale reactor. Radiotracer 198Au was used to trace the liquid phase of the industrial scale continuous three tube pulp digester. The radiotracer was injected instantaneously as an impulse input in the liquid phase and concentration versus time data were collected at the inlet and outlet of each tube using a data acquisition system. The flow modeling of continuous pulp digester has been done in two ways. Firstly, the whole digester was considered a single reactor. Secondly, each tube of the digester was considered a single reactor separately. For the second case, the convolution procedure was opted to deal with a non-ideal input signal for the second and third tubes. Axial dispersion model and tank in series with a back-mixing model were used to simulate the experimental data. Mean residence time and Peclet numbers were calculated for each tube and the whole digester.